Radiographical, Histomorphological and Histochemical study of pharyngeal tonsil in adult Indigenous sheep(Ovis aries) and goat(Capra aegagrus hircus) : a comparative study (NTU Journal of Agriculture and Veterinary Science, 2025)
The pharyngeal tonsils are lymphoepithelial structures at the opening of the respiratory system. They are covered by pseudostratified columnar epithelium and have longitudinal and transverse crypts going through them. Nodular and diffuse lymphoid tissue, connective tissue, and clusters of secretory units, surrounded by muscle and adipose tissue, intersperse these crypts.We conducted the study on 12 sheep and 12 local goats, all clinically healthy, adult , and slaughtered at the Mosul slaughterhouse. We fixed the samples in 10% neutral buffered formalin.The results of the X-ray study revealed that the pharyngeal tonsils of sheep and local goats are hollow in some parts but clearly visible in the posterior part of the nasopharynx, caudal to the vomer bone. Using routine and special stains for histological and histochemical studies, researchers found two types of epithelium in the tonsils of sheep and goats: reticular and non-reticular. The thickness of these epithelium types was different. We noted the interspersion of crypts of varying lengths in the epithelium, the presence of primary and secondary follicles, and dark marginal zones of lymphocytes and germinal centers. The lamina propria-submucosa had collagenous and reticular fibers under the epithelium and around the follicles. It also had adipose and glandular tissues, which were shown by secretory units and their ducts. The periodic acid-Schiff (PAS) stain and Alcian blue both showed that these tissues were present. There were high-endothelial venules next to the follicles that helped lymphocytes move through both the reticular and non-reticular epithelium.Our current study concludes that there are differences in the location, histological, and histochemical structure of the pharyngeal tonsils between sheep and goats.